Inappropriate posture habits and pain in adolescents - Faria, Daniela Aparecida de (2021)
This study aimed to describe inappropriate postural habits and the presence of pain in adolescent students. A cross-sectional, exploratory, descriptive study with a quantitative approach was carried out. The sample consisted of 74 adolescents, aged 10 to 19 years. Data collection was performed using the BackPEI Test (Back Pain and Body Posture Evaluation Instrument). Data analysis revealed the occurrence of habits of inappropriate posture in activities such as reading in bed, sitting at the table to write or talking, using the computer, picking up objects on the floor. The presence of pain was possibly associated with inadequate posture. The results suggest an urgent need to develop educational and preventive programs in the school environment for the promotion and prevention of bodily pain and describe inappropriate postural habits in adolescents.